Regulation of Flowering Time by Improving Leaf Health Markers and Expansion by Salicylic Acid Treatment: A New Approach to Induce Flowering in Malus domestica - Shah, Kamran; An, Na; Kamanova, Svetlana; Chen, Lijuan; Jia, Peng; Zhang, Chenguang; Mobeen Tahir, Muhammad; Han, Mingyu; Ding, Yuduan; Ren, Xiaolin; Xing, Libo (Frontiers in Plant Science, 2021)
In the external coincidence model, internal and external molecular signals provided by the circadian clock and sunlight, respectively, are required to induce flowering. Salicylic acid (SA) applications during floral induction have multiple effects. In current study, Malus × domestica plants were exposed to SA during flower-induction stage to analyze the effect on various health markers and flowering. A total of fifty-six equal-sized and about 7-year-old Fuji/M9 trees were randomly divided into two groups. The first group (SA-treated) was sprayed with 4 mM SA solution, while the second group was sprayed with distilled water which served as control (CK). The SA applications increased various leaf pigments. Abiotic stress markers were increased in CK during flower-induction stage. In the SA-treated group, non-enzymatic antioxidants increased, whereas in the control group, enzymatic antioxidants increased during the flower-induction stage. Histo-morphometric properties of leaves were significantly improved in the SA-treated group. Relative expression mRNA levels of MdMED80, -81, -3 and -41 were significantly increased in SA-treated leaves, leading to an early and increased flowering phenotype. Thus, SA increased leaf expansion and health-related marker levels, which lead to early induction of flowering in M. domestica. Overall, our work established a role for leaf health assessments in the regulation of flowering in M. domestica.